Effect of Mud Compositions on the Rheological Behavior - Al-Hiti, Akram H. A.; Al-Hashimi, Wisam (Iraqi Journal of Chemical and Petroleum Engineering, 2001)
The aim of this work is to study the effect of mud compositions on it’s rheological behavior under high temperature conditions. Seventeen samples of five types of water base mud in which (fresh water bentonite mud. Lignosulphonate mud, gypsum mud, polymer mud, and salt saturated mud) were tested with different temperatures using the fann viscometer model 50-c. All the tested samples, except the fresh water bentonite mud, have the same trend reduction in both plastic viscosity and yield point with increasing temperature. Six rheological models has been adapted: Bingham plastic, power law, Casson model represent the laboratory data accurately